2017
DOI: 10.1021/jacs.7b06044
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylation of Alkyl Radicals in Aqueous Solution

Abstract: The copper-mediated trifluoromethylation of alkyl radicals is described. The combination of EtSiH and KSO initiates the radical reactions of alkyl bromides or iodides with BPyCu(CF) (BPy = 2,2'-bipyridine) in aqueous acetone at room temperature to afford the corresponding trifluoromethylation products in good yield. The protocol is applicable to various primary and secondary alkyl halides and exhibits wide functional group compatibility. A mechanism involving trifluoromethyl group transfer from Cu(II)-CF inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 36 publications
5
92
0
2
Order By: Relevance
“…[34][35][36][37] The N-centered radical A abstracts a benzylic hydrogen atom to generate the corresponding benzyl radical. The benzyl radical is then intercepted by Cu(II)-CF 3 either by direct CF 3 group transfer 28,29 or by the formation of benzylcopper(III) intermediate followed by reductive elimination, [30][31][32] resulting in the formation of the corresponding trifluoromethylation product and regeneration of the Cu(I) catalyst. However, this catalytic cycle is challenging given that the oxidation of CF 3 anions to CF 3 radicals by Cu(II) is well documented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36][37] The N-centered radical A abstracts a benzylic hydrogen atom to generate the corresponding benzyl radical. The benzyl radical is then intercepted by Cu(II)-CF 3 either by direct CF 3 group transfer 28,29 or by the formation of benzylcopper(III) intermediate followed by reductive elimination, [30][31][32] resulting in the formation of the corresponding trifluoromethylation product and regeneration of the Cu(I) catalyst. However, this catalytic cycle is challenging given that the oxidation of CF 3 anions to CF 3 radicals by Cu(II) is well documented.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22] The underdevelopment of C(sp 3 )-H trifluoromethylation should be largely attributed to the lack of methods for trifluoromethylation of alkyl radicals. [28][29][30] We recently introduced the trifluoromethylation of alkyl halides by reaction with (bpy)Cu(CF 3 ) 3 (bpy = 2,2 0 -bipyridine), K 2 S 2 O 8 , and Et 3 SiH in aqueous solution and proposed the mechanism of CF 3 transfer to alkyl radicals from Cu(II)-CF 3 intermediates. 28 The method was then extended to AgNO 3 -and K 2 S 2 O 8 -mediated decarboxylative trifluoromethylation of aliphatic carboxylic acids with (bpy)Cu(CF 3 ) 3 and ZnMe 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulated that direct Csp 3 −H trifluoromethylation reactions could be feasible if a suitable CF 3 source is identified that can transfer CF 3 groups to alkyl radicals. Recently, elegant work of Li has shown that a Cu III −CF 3 complex can efficiently transfer a CF 3 group to an alkyl radical . Inspired by these results, we report herein a general method for the direct trifluoromethylation of benzylic Csp 3 −H bonds (Scheme ).…”
Section: Methodsmentioning
confidence: 98%
“…[3] Aside from ah andful of CF 3 -radical-based functionalizations of structurally elaborated styrene derivatives, [4] these molecules could be created either by direct trifluoromethylation of aliphatic skeletons [5] or through crosscoupling using a-CF 3 -derived precursors (Scheme 1a). [6,[12][13][14][15][16] With Lisp ioneering work on trifluoromethylation of alkyl radicals using Grushinsreagent, [7] thegroups of MacMillan, [8] Cook, [9] and Liu, [10] developed decarboxylative and benzylic C À Ht rifluoromethylation protocols,a lthough the employment of expensive CF 3 reagents,aswell as restricted substrate scope,are still concerns.…”
mentioning
confidence: 99%